Pengelolaan Bank Sampah Dalam Upaya Menjaga Irigasi Kelurahan Talang Dantuk Seluma - Kiliranti, Yesi; Vitriani, Leka; Icandi, Igor; Delvianah, Pofy; Fradata, Rahmadan; Ninosari, Devina; Syafran, Ahmad; Lorita, Evi (Jurnal Gotong Royong, 2026)
Community service via Thematic KKN from Bengkulu University established a community waste bank in Talang Dantuk Kelurahan, Seluma Subdistrict, Seluma Regency, to address irrigation pollution from household waste. Participatory methods included socialization, organic-inorganic waste sorting training, and weekly collection operations per Minister of Environment Regulation No. P.95/2016. Results showed active resident participation, reduced wild waste in irrigation, and potential additional income. The waste bank alleviates landfill burdens, protects agricultural infrastructure, and fosters independent environmental awareness. Challenges like limited KKN duration and weather were managed through community coordination. This initiative is recommended for replication in other villages to promote sustainable waste management.